'Touching people in relationships': a qualitative study of close relationships for people with an intellectual disability. Issue 23 (9th October 2013) - Sullivan, Faye; Bowden, Keith; McKenzie, Karen; Quayle, Ethel
Abstract : Aims and objectives: To explore the experiences and perceptions of close and sexual relationships of people with an intellectual disability. Background: Positive interpersonal relationships are beneficial for people with an intellectual disability, acting as a protective barrier against, social stigma and negative outcomes such as physical and mental health problems. The social networks of people with an intellectual disability are, however, often more restricted than those of the general population. There has been very little research exploring the views and experiences of people with an intellectual disability about social and sexual relationships. Design: Exploratory study using a qualitative research design. Methods: Semi‐structured interviews were conducted with 10 (6 male, 4 female) participants. Data were analysed using interpretive phenomenological analysis. Results: 'Touching other people in relationships' was identified as a superordinate theme. The theme was represented by five subthemes: 'Is wrong'; 'Unsafe to talk about'; 'Suggesting is safe'; 'No freedom or fun'; and 'Being touched'. The findings presented are drawn from a larger qualitative study. Conclusions: The findings highlight the importance of touch and sexual behaviours in the close relationships of participants. Negative perceptions were observed to surround sexual behaviours. Rules and restrictions regarding physical contact were also described. Relevance to clinical practice: Disseminating these findings may increase awareness of the importance of physical contact in the close relationships of people with an intellectual disability and promote positive support arrangements.